The Effectiveness of Village Fund Management on Community Welfare in Kedungringin Village, Suruh District, Semarang District 2016-2019 - Yunita Rhoman Maulany; Fafurida Fafurida (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
The village is a residential area where most of the population makes a living in agriculture. Most of Indonesia's population are residents who live in rural areas. The village government can use village funds as a source of financing for village household needs in order to improve the welfare of the village community. This study aims to analyze the effectiveness of village fund management on the welfare of village communities in Kedungringin Village, Suruh District, Semarang Regency. Data collection methods used are through observation and literature study, then analyzed using descriptive qualitative data analysis methods. The results of the study were the management of village funds based on indicators of goal achievement, timeliness, benefits, and results in accordance with community expectations. As well as village funds also play a role in developing the economy of the village community so that it can improve the welfare of the village community through the existence of development and community empowerment programs.